SAW filters with fan-shaped transducers - ZABUZOW, S. A.; KONOVALOVA, L. P.; SMIRNOV, U. G. (Archives of Acoustics, 1991)
The results of the study of frequency characteristics of SAW filters with multifinger fan-shaped transducers (FST) are presented. Practically useful relations determining the FST directivity diagram and the main filter characteristics dependent on FST layout and the distance between them are obtained.